Predicting Construction Costs with Machine Learning: A Comparative Study on Ensemble and Linear Models - Chen, Lifei; Tiang, Sew Sun; Chong, Kim Soon; Sharma, Abhishek; Berghout, Tarek; Lim, Wei Hong (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
Accurate prediction of construction costs plays a pivotal role in ensuring successful project delivery, influencing budget formulation, resource allocation, and financial risk management. However, traditional estimation methods often struggle to handle complex, nonlinear relationships inherent in construction datasets. This study proposes a process innovation by systematically evaluating six machine learning (ML) models, i.e., Ridge Regression, Lasso Regression, Elastic Net, K-Nearest Neighbors (KNN), XGBoost, and CatBoost, on a standardized RSMeans dataset comprising 4,477 real-world construction data points. The primary aim is to benchmark the predictive performance, generalizability, and stability of both linear and ensemble models in construction cost forecasting. Each model is subjected to rigorous hyperparameter tuning using grid search with 5-fold cross-validation. Performance is assessed using R² (coefficient of determination), RMSE (root mean squared error), and MBE (mean bias error), while confidence intervals are computed to quantify predictive uncertainty. Results indicate that linear models achieve modest accuracy (R² ≈ 0.83), but struggle to model nonlinear interactions. In contrast, ensemble-based models significantly outperform , i.e., XGBoost and CatBoost achieve R² values of 0.988 and 0.987, respectively, RMSE values below 0.5, and near-zero MBE. Moreover, confidence interval visualization and feature importance analysis provide transparency and interpretability, enhancing the models practical applicability. Unlike prior studies that compare models in isolation, this work introduces a unified, interpretable framework and highlights the trade-offs between accuracy, overfitting, and deployment readiness. The findings have real-world implications for contractors, project managers, and cost engineers seeking reliable, data-driven decision support systems. In summary, this study present a scalable and robust ML-based framework that facilitate process innovation in construction cost estimation, paving the way for more intelligent, efficient, and risk-aware construction project management.